Bottom-up physiologically based pharmacokinetic modelling for predicting the human pharmacokinetic profiles of the ester prodrug MGS0274 and its active metabolite MGS0008, a metabotropic glutamate 2/3 receptor agonist. (1st February 2022) - Ochi, Motoki; Kinoshita, Kohnosuke; Yamaguchi, Jun-ichi; Endo, Hiromi
Abstract: For ester prodrugs that are used to improve the gastrointestinal absorption of highly hydrophilic, pharmacologically active substances, it is challenging to predict the human pharmacokinetics (PK) of the prodrugs and their parent compounds using only preclinical data. This research was aimed at constructing a PBPK model for predicting the human PK of the ester prodrug MGS0274 and its parent compound MGS0008 after a single oral administration of MGS0274 besylate. First, we identified carboxylesterase 1 (CES1) as the major enzyme involved in the hydrolysis of MGS0274. Second, we constructed a new compartment model to estimate the passive diffusion clearance (CLpd ) of MGS0008, a critical parameter for predicting the PK of highly hydrophilic compounds, based on in vivo monkey PK data. Finally, we constructed a permeability-limited liver PBPK model incorporating the CLpd assumed to be the same in humans. We confirmed that our method reliably predicted the human PK and that the estimated CLpd was comparable to that calculated retrospectively using the PBPK model, suggesting that the methodology for estimating the CLpd was valid. Our proposed methodology is expected to be helpful for human PK prediction of ester prodrugs hydrolysed by CES1 and their hydrophilic parent compounds even during the preclinical phase.